Effect of concentration on the photophysics of dyes in light-scattering materials. - Rodríguez, H.B. (2013)
Photoactive materials based on dye molecules incorporated into thin films or bulk solids are useful for applications as photosensitization, photocatalysis, solar cell sensitization and fluorescent labeling, among others. In most cases, high concentrations of dyes are desirable to maximize light absorption. Under these circumstances, the proximity of dye molecules leads to the formation of aggregates and statistical traps, which dissipate the excitation energy and lower the population of excited states. The search for enhancement of light collection, avoiding energy wasting requires accounting the photophysical parameters quantitatively, including the determination of quantum yields, complicated by the presence of light scattering when particulate materials are considered. In this work we summarize recent advances on the photophysics of dyes in light-scattering materials, with particular focus on the effect of dye concentration. We show how experimental reflectance, fluorescence and laser-induced optoacoustic spectroscopy data can be used together with theoretical models for the quantitative evaluation of inner filter effects, fluorescence and triplet formation quantum yields and energy transfer efficiencies. © 2013 The American Society of Photobiology.